A LABORATORY APPARATUS FOR THE DETERMINATION OF THE ANCHORAGE CAPACITY OF ROCK BOLTS. EVALUATION OF ROCK BOLT ANCHORAGES. - Tiseo,Benedict (1969)
The increasing use of rock bolts as a means of support in underground construction requires additional knowledge on the most efficient rock bolt systems in different rock types. This information is normally obtained from field pull tests at the beginning of construction. Savings in both time and money could be realized if the optimum rock bolt system could be determined prior to construction. A rock bolt pull test apparatus and procedure have been developed that enable the anchorage capacities of expansion shell rock bolt anchor systems to be determined in the laboratory. In the apparatus, expansion shell rock bolt anchors are set in a hole in a six-inch-diameter, 15-inch long rock core that is cast into a steel confining cylinder. The reaction for pulling of the rock bolt is jacked against the rock core in which the anchor is set. Measurements are made of both the bolt and anchor displacement. (Author)